The Correlation Between Nurse Competence and Nurse Preparedness in The Disaster of The Covid-19 Pandemic - Irwan Budiana; Krispina Owa; Yoseph Woge; Raimunda Woga (Jurusan Keperawatan, Poltekkes Kemenkes Mataram, 2022)
The prevention and control of the Covid-19 pandemic disaster that has been carried out so far still has various forms of challenges so that positive cases of Covid-19 have the potential to continue to increase every day. One of the ways to handle the Covid-19 pandemic disaster in hospitals is by nursing who have competencies that have been set according to standards. The purpose of this study was to determine the correlation between nurse competence and preparedness in dealing with the Covid-19 pandemic disaster at the Regional Hospital of Ende Regency, East Nusa Tenggara Province. This research used a quantitative design method with a correlational analytic approach. The technique of determining respondents used purposive sampling method.The results of the Spearman Rank variable test of knowledge, attitude and skills show no significant correlation to preparedness in dealing with non-natural disasters Covid 19 with p-value > 0.05. 0.097 for the p-value of the knowledge, 0.188 for the p-value of attitude and 0.720 p-value for skill. Meanwhile, the direction of the correlation between the three variables has a undirectional nature in accordance with the positive value of the correlation coefficient. The correlation level of the three variables were moderate level of correlation (0.308), very weak correlation level (0.247) and very weak correlation level (0.068) for knowledge, attitude and skills, respectively. The competence of nurses as part of the Covid 19 pandemic response team needs to be improved in the hope of minimizing casualties and greater material and non-material loss.